MODEL HUBUNGAN KEPUASAN KERJA, KOMITMEN ORGANISASIONAL DAN STRES KERJA TERHADAP TURNOVER INTENTION - Destiyana, Bunga; Sarnianto, Prih; Deriawan, Deriawan (Economic Faculty, Attahiriyah Islamic University, 2019)
The objective of this study is to analyze the factors that can influence turnover intention. This research was conducted at the drug registration staff of pharmaceutical companies with seventy respondents who were carrying out their duties at BPOM. Three independent variables in this research namely job satisfaction, organizational commitment, and job stress were examined to determine their relationship with the dependent variable namely turnover intention. Regression analysis of the primary data obtained shows that job stress has a significant effect on the turnover intention of staff registering drugs to other pharmaceutical companies. Two other variables, namely job satisfaction and organizational commitment have no effect on turnover intention of staff registration drugs from pharmaceutical companies. Keywords: job stress, organizational commitment, job satisfaction, turnover intention